2016
DOI: 10.1140/epjc/s10052-016-3941-z
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological implications of the intrinsic charm in the Z boson production at the LHC

Abstract: In this paper we study the Z , Z + jet, Z + c, and Z + c+ jet production in pp collisions at the LHC considering different models for the intrinsic charm content of the proton. We analyze the impact of the intrinsic charm in the rapidity and transverse momentum distributions for these different processes. Our results indicated that differently from the other processes, the Z +c cross section is strongly affected by the presence of the intrinsic charm. Moreover, we propose the analysis of the ratiosand we demon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Our conclusion at the moment is that the LHC inclusive W and Z production cross sections may provide helpful correlated constraints on m c and x IC in the future. We may also consider more exclusive scattering processes [120][121][122][123][124][125][126][127]129] to look for evidence of the IC in the LHC environment.…”
Section: Impact Of Ic On Electroweak Z and H Boson Production Cross Smentioning
confidence: 99%
“…Our conclusion at the moment is that the LHC inclusive W and Z production cross sections may provide helpful correlated constraints on m c and x IC in the future. We may also consider more exclusive scattering processes [120][121][122][123][124][125][126][127]129] to look for evidence of the IC in the LHC environment.…”
Section: Impact Of Ic On Electroweak Z and H Boson Production Cross Smentioning
confidence: 99%
“…Calculations come from the radiatively generated charm PDF (CTEQ66), the sea-like PDF (CTEQ66c4) and the BHPS PDF (CTEQ66c2) also for P cc N = 3.5% and found that the IC manifestation could be measured with both the ATLAS and CMS detectors. [18] studied, within various models, the impact of the IC on the rapidity and transverse momentum distribution in the Z-boson production in proton-proton collisions at the LHC, and showed that the Z + c cross section is significantly sensitive to the presence of the IC.…”
Section: Referencementioning
confidence: 99%
“…More recently Dulat and collaborators [12] analyzed the parton distribution function (PDF) of the proton based on the NNLO approximation of perturbative QCD and included the combined H1 and ZEUS data [13], reaching the conclusion that the PDF uncertainties are just as large as the IC effects. In summary, the nucleon's IC remains elusive, however several studies predict measurable effects of such possible components in the ongoing and/ or forthcoming experiments at the LHC [12,[14][15][16][17][18][19][20] and RHIC [15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [51][52][53] the results of c-jet production accompanied by vector bosons Z, W ± is stud-ied by using the intrinsic charm quark component. The impact of IC contributions for the prediction of γ + cjet production in pp collisions at the LHC is reported in Ref.…”
mentioning
confidence: 99%